2019
DOI: 10.1021/acsami.9b02104
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 2D Antimony(III) Selenide Nanosheets for Highly Efficient Photonic Cancer Theranostics

Abstract: Photonic cancer hyperthermia has been considered to be one of the most representative noninvasive cancer treatments with high therapeutic efficiency and biosafety. However, it still remains a crucial challenge to develop efficient photothermal nanoagents with satisfactory photothermal performance and biocompatibility, among which two-dimensional (2D) ultrathin nanosheets have recently been regarded as the promising multifunctional theranostic agents for photothermal tumor ablation. In this work, we report, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Cancer represents a devastating disease without satisfactory pharmacotherapeutic strategies at the current stage, which has relentlessly taken away countless lives due to worrisome morbidity and mortality. , Irritatingly, traditional cancer-therapeutic strategies suffer from the inevitable hurdles, including non-negligible therapeutic resistance, noticeable side effects, and undesired therapeutic outcomes, which have substantially hindered the creation and implementation of their preclinical and clinical uses. To ameliorate and combat the drawbacks of the aforementioned cancer treatment strategies, substantial efforts have been devoted to the exploration of innovative approaches for minimal invasiveness and highly selective enhancement of monotherapy based on rationally engineered nanomedicines. , Especially, near-infrared (NIR)-induced and theranostic nanosystem-mediated photonic tumor hyperthermia has been demonstrated to be a local noninvasive therapeutic paradigm due to its distinctive merits, including minimal invasiveness, a steerable process, desired therapeutic effects, and negligible side effects. …”
Section: Introductionmentioning
confidence: 99%
“…Cancer represents a devastating disease without satisfactory pharmacotherapeutic strategies at the current stage, which has relentlessly taken away countless lives due to worrisome morbidity and mortality. , Irritatingly, traditional cancer-therapeutic strategies suffer from the inevitable hurdles, including non-negligible therapeutic resistance, noticeable side effects, and undesired therapeutic outcomes, which have substantially hindered the creation and implementation of their preclinical and clinical uses. To ameliorate and combat the drawbacks of the aforementioned cancer treatment strategies, substantial efforts have been devoted to the exploration of innovative approaches for minimal invasiveness and highly selective enhancement of monotherapy based on rationally engineered nanomedicines. , Especially, near-infrared (NIR)-induced and theranostic nanosystem-mediated photonic tumor hyperthermia has been demonstrated to be a local noninvasive therapeutic paradigm due to its distinctive merits, including minimal invasiveness, a steerable process, desired therapeutic effects, and negligible side effects. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhou et al demonstrated that the photothermal effect of nanostructured Sb 2 Se 3 provided these binary Sb-based nanoparticles with promising potentials in cancer theranostics . They combined liquid nitrogen pretreatment and the freezing–thawing approach and obtained 2D Sb 2 Se 3 nanosheets (NSs), which were further decorated with poly­(vinylpyrrolidone) (PVP) to improve biocompatibility (Figure ).…”
Section: Antimony-based Nanomaterialsmentioning
confidence: 61%
“…PTT 是依靠光热转换剂(Photothermal transducing agents,PTA)在肿瘤内积累并将光能转化为热 能,通过产生热量而杀死肿瘤细胞,比传统肿瘤治 疗方式的副作用小 [46][47][48][49][50][51] 。 外界光照射和 PTA 是决定 PTT 效果的主要因素 [52] 。对于 PTA 来说,有两个基 本参数影响其 PTT 效果,一个是 PTA 对光的吸收 能力,由消光系数决定,另一个是在外界光照射下 PTA 产生热量的能力,由光热转换效率决定 [40,53] 。 Geng 课题组 [54] 将 Ti3C2 纳米片作为 PTA 用于 肿瘤治疗研究, 其制备的 Ti3C2 纳米片在 808 nm NIR 光照射下质量消光系数为 29.1 Lg - Requiring inert protective gas, under high temperature condition [19,38] Alkali assisted hydrothermal…”
Section: 光热治疗unclassified